2023
DOI: 10.1111/1759-7714.15135
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound‐guided thoracic paravertebral block on perioperative analgesia in elderly patients undergoing video‐assisted thoracic lobectomy in China: An interventional clinical randomized controlled trial

Chanjuan Gong,
Rong Ma,
Bing Li
et al.

Abstract: BackgroundThe aim of this study was to investigate the analgesic effect and safety of ultrasound‐guided thoracic paravertebral block (UG‐TPVB) in Chinese elderly patients undergoing video‐assisted thoracic lobectomy (VATL) and to study the influence of aging factors on these effects.MethodsThis study was a single‐center, single‐blind, prospective, randomized, controlled trial. A total of 300 patients scheduled for VATL were recruited and randomly divided into the UG‐TPVB group (T group) and conventional anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…To ensure the effectiveness and safety of postoperative analgesia, TPVB was performed by the same experienced anesthesiologists under the guidance of ultrasound. Numerous studies have confirmed that TPVB can reduce postoperative acute pain, mainly caused by the chest drain and opioid sparing after thoracic surgery [21,22]. One previous study showed that general anesthesia combined with TPVB can reduce postoperative pulmonary complications by reducing postoperative pain in geriatric patients undergoing thoracic surgery [23].…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the effectiveness and safety of postoperative analgesia, TPVB was performed by the same experienced anesthesiologists under the guidance of ultrasound. Numerous studies have confirmed that TPVB can reduce postoperative acute pain, mainly caused by the chest drain and opioid sparing after thoracic surgery [21,22]. One previous study showed that general anesthesia combined with TPVB can reduce postoperative pulmonary complications by reducing postoperative pain in geriatric patients undergoing thoracic surgery [23].…”
Section: Discussionmentioning
confidence: 99%